Intelligent Smart Contracts for Innovative Supply Chain Management - Bottoni, Paolo; Gessa, Nicola; Massa, Gilda; Pareschi, Remo; Selim, Hesham; Arcuri, Enrico (Frontiers in Blockchain, 2020)
We propose blockchains and smart contracts as enabling technologies for an innovative type of supply chain management, with the goal of achieving higher levels of collaboration between the companies participating in the chain, which in turn pays in the form of higher levels of profitability and economic health for the participating enterprises. Our proposal goes far beyond simply using blockchains as decentralized systems to track the origin and delivery of goods, which is what most of the current blockchain projects on supply chains are focused on. In fact, we introduce a type of smart contract aimed to solve two of the main problems that hinder the efficiency and effectiveness of supply chains, namely trust and coordination. Solving the problem of trust amounts to the capability of establishing quickly and cheaply contractual relationships based on convergent business needs among parties that may not know each other, and therefore need to protect themselves from opportunistic or incorrect behavior. Solving the problem of coordination consists in creating, at convenient management costs, a control system capable of directing the objectives of the supply chain as a whole, so as to achieve a greater common good in the medium term, as an alternative to the state of affairs in which each participant pursues, on its own behalf, lower but immediate returns. Our smart contracts for innovative supply chain management replace human coordinators in tackling the problems above, thus eliminating one major obstacle to their effective solution, namely the need to trust the coordinator itself. Furthermore, in this way, by automating the process of coordination, they unburden the supply chain of a considerable management cost. Contracts of this kind not only automate contract execution as in standard smart contracts, but also adjust costs and compensations of the members of a supply chain, effectively taking up the role that was of human coordinators. Thus, we refer to them as “intelligent smart contracts”. In the course of the paper, we will illustrate an innovative supply chain architecture based on intelligent smart contracts running on blockchain, we will detail the algorithmic methodologies underlying the decision-making process of these contracts